Prevention of Retinochoroiditis in Congenital Toxoplasmosis Europe Versus South America (2011)
Congenital toxoplasmosis remains a public health problem throughout the world. Long-term longitudinal studies are still needed to argument controversial screening and treatment strategies and to enable to accurately counsel parents. We conducted a prospective cohort study over 16 years in Marseilles, France. Seronegative pregnant women underwent monthly serological testing. Children were treated antenatally with rovamycine as soon as maternal infection was detected and with pyrimethamine and sulfadoxine in case of positive Toxoplasma PCR on amniotic fluid. Postnatal treatment with pyrimethamine and sulfadoxine was systematically prescribed for one year and possibly continued at the physician discretion. 127 children were included. 24 children (18.9%) presented ocular lesions causing visual impairment in eight cases. Eleven children (8.7%) presented with ocular lesions at birth, mostly macular. Sixteen children (12.6%) developed ocular lesions during follow-up, mostly peripheral. The first ocular lesion could occur as late as 12 years after birth. No significant risk factor of chorioretinitis was identified including gestational age at infection, type of antenatal treatment and shorter postnatal treatment. These results confirm the overall good prognosis of congenital toxoplasmosis in Europe but highlight though a low risk of late ocular manifestation. Chorioretinitis affected 18.9% of children suffering from congenital toxoplasmosis despite antenatal and neonatal screening associated with early treatment. Long-standing follow-up is needed because first lesion can occur as late as 12 years after birth. Late lesions were less often macular but nevertheless caused sometimes visual impairment.